Quantitative analysis of normal and pathologic adrenal glands with 18F-FDOPA PET/CT: focus on pheochromocytomas. Issue 9 (September 2017) - Moreau, Aurélie; Giraudet, Anne L.; Kryza, David; Borson-Chazot, Françoise; Bournaud, Claire; Mognetti, Thomas; Lifante, Jean-Christophe; Combemale, Patrick; Giammarile, Francesco; Houzard, Claire
Abstract : Introduction: Many studies have reported the high performance of 6-fluorine-18-fluorodihydroxyphenilalanine ( 18 F-FDOPA) PET/CT in the diagnosis of pheochromocytomas but nobody seems to have investigated physiological and pathological adrenal glands from a quantitative point of view. The purpose of the present study was to assess the quantitative 18 F-FDOPA uptake of normal and pathologic adrenal glands and to establish thresholds to characterize pheochromocytomas. We were especially interested in characterizing the remaining adrenal glands captation after an adrenalectomy. Patients and methods: We reviewed 112 18 F-FDOPA PET/CT scans taken for different indications. A total of 212 adrenal glands, of which 17 were pheochromocytomas, were analyzed on the basis of their functional and morphological features. The final diagnosis was based on histologic proof when available (six pheochromocytomas) or after synthesis of clinical, biological, morphological, and functional results. Maximum standardized uptake value (SUVmax ), mediastinum, and liver ratios in case of pheochromocytomas, adenomas, and solitary adrenal glands were determined and compared with those of healthy glands. Receiver operating characteristic curves were determined and areas under the curve were compared for different cutoffs of each index. Results: Pheochromocytomas demonstrated a higher 18 F-FDOPA uptake compared with normal adrenal glands (mean SUVmax : 7.5, SD 4.0, range: 3.5–20.0 vs. mean SUVmax : 2.6, SD: 0.8, range: 1.0–6.9) ( P <0.0001). An SUVmax threshold of 4.2 has a sensitivity and specificity of 94 and 98%, respectively. The areas under the curve were 0.988, 0.991, and 0.987 for an SUVmax of 4.2, a mediastinum ratio of 3.0, and a liver ratio of 1.7, respectively. A large number of nonsecreting pheochromocytomas were noticed. On the basis of the SUVmax no statistically significant difference was found between secreting (SUVmax : 8.9, SD: 5.3) and nonsecreting pheochromocytomas (SUVmax : 5.1, SD: 0.9) ( P =0.141). After unilateral adrenalectomy, solitary glands presented no increased uptake compared with healthy adrenal glands. An unexpected lower captation was also observed (SUVmax : 2.0, P =0.047). Conclusion: We confirm the high affinity of 18 F-FDOPA for secreting or nonsecreting pheochromocytoma. Indeed within a series of various adrenal glands, only these tumors presented a significant increased uptake compared with normal adrenal glands. Because of a high rate of nonhypersecreting lesions, 18 F-FDOPA can act as a surrogate to biological assays. After an adrenalectomy, the remaining glands did not demonstrate compensatory accumulation of 18 F-FDOPA. To our knowledge this last point has never been addressed.